Study on suppression of otoacoustic emissions: lateral domain - Massola de Oliveira, Jerusa Roberta [UNESP] (2011)
Abstract A pon stimulation by contralateral, ipsilateral or bilateral noise, the medial olivocochlear efferent tract changes the amplitude of otoacoustic emissions relative to the tested ear, reducing or removing it; this resulted in a reduction/suppression effect of otoacoustic emissions. Differences in patterns of elimination/reduction of otoacoustic emissions between ears have been documented worldwide; there are, however, no Brazilian studies investigating the effect of lateral dominance. Aims To compare the effect of the presence of deletion/reduction of otoacoustic emissions and their amplitude relative to lateral dominance in normal hearing adults. Methods A clinical and experimental study. The sample comprised 75 individuals. The methodology was conventional - linear click intensity of 60 dB SPL; white noise was contralateral stimulation at 60 dB SPL. Description of results There were no statistically significant differences between right and left ear results, in terms of asymmetry of the degree of otoacoustic emissions and the presence of suppression/reduction. Conclusion There is no lateral dominance in the degree of otoacoustic emissions in the presence of suppression/reduction in the study population.